2001
DOI: 10.1063/1.1409585
|View full text |Cite
|
Sign up to set email alerts
|

Charging effects in gold nanoclusters grown on octanedithiol layers

Abstract: Strong interaction of gold with the terminal sulfur atoms of dithiol molecules on Au(111) effectively suppresses the penetration of deposited Au atoms through the dithiol layer and results in the formation of homogeneous Au nanoclusters. These nanoclusters, 10–15 Å (σ<2 Å) in height, spread over the surface with a density of ∼1.2×1013/cm2 for coverage between 0.25–2.5 monolayers. Decoupling of the clusters from Au(111) by the octanedithiol layer (∼12 Å in thickness) and the small self-capacitance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 8 publications
0
79
0
1
Order By: Relevance
“…2,3,[5][6][7] In contrast, when they are deposited on an alkanedithiol SAM with a thiol end group pointing up, metal nanoparticles are formed on top of the SAM. 1,2,4,8 This is due to the strong interaction between deposited metal nanoparticles and thiol end groups, which reduces the possibility of diffusion of deposited metal nanoparticles into the SAM. Dithiol SAMs are also used for attracting and fixing the metal nanoparticles on the surface from a solution.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,[5][6][7] In contrast, when they are deposited on an alkanedithiol SAM with a thiol end group pointing up, metal nanoparticles are formed on top of the SAM. 1,2,4,8 This is due to the strong interaction between deposited metal nanoparticles and thiol end groups, which reduces the possibility of diffusion of deposited metal nanoparticles into the SAM. Dithiol SAMs are also used for attracting and fixing the metal nanoparticles on the surface from a solution.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the electrostatic energy of a cluster changes dramatically upon the charge transfer. Without the application of a sufficient bias voltage, electron transfer is suppressed (Coulomb blockade) [13]. This effect is predominantly observed with a near-zero bias voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Dithiol SAMs have been utilized to make nanodevices, for measurements of electricity transport, and for multilayer formation. [4][5][6][7][14][15][16][17]22,23,25,[30][31][32][33][34][35][36][37][38][39][40] So far, most studies have focused on their use either as a linker for metal nanoparticles to study charge transfer or as a spacer for multilayer formation. Compared to the well-studied monothiolate SAMs, not many reports have focused on the growth and structure of dithiol SAMs, and disagreements exist among the literature reported concerning the preparation of dithiol SAMs, the resulting structures, and the quality of dithiol SAMs.…”
Section: Introductionmentioning
confidence: 99%
“…Scoles et al carefully studied monolayers of HSC 6 SH on Au(111) single-crystal substrates by means of several surface science techniques in vacuum, and reported that the molecules lay prone in a striped arrangement with an inter-row spacing of 5 Å from the gas phase and that no evidence of nucleation of other ordered phases was found in different growth protocols, including liquid-phase deposition of 4-16 h in a millimolar ethanolic solution. 41 The results were then explained by the strong molecule/substrate interaction in the striped phases, which was interpreted as a consequence of the strong, but, not sitespecific, interaction of both sulfurs with the gold surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation